Physical Wellbeing in Cervical and Breast Cancer Survivors: A Cross-sectional Study in Surabaya, Indonesia - Purnama Sari, Ni Putu Wulan (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Cervical and breast cancer are the two top leading cases of female cancer worldwide. Both cases share some similar clinical manifestations as specific symptoms of cancer. Physical wellbeing often decreased as frequent symptoms appear. This study aimed to compare and analyze the physical wellbeing among cervical cancer and breast cancer survivors (CCS and BCS).Methods: This cross-sectional study involved 47 CCS and 58 BCS in the district of Rangkah, Gading, and Pacarkeling, Surabaya, Indonesia. Instrument of Quality of Life – Cancer Survivors (QOL-CS) was used for data collection. Independent sample T test and Mann-Whitney U test were used in data analysis (α< .05). Results: More severe fatigue, appetite changes, pain, sleep disturbance, constipation, nausea-vomiting, and menstrual changes were found in CCS. More poor perceived health status and optimal physical wellbeing were found in BCS. Overall, most sufficient physical wellbeing was found in both groups. There were significant differences of fatigue, pain, sleep disturbance, appetite changes, constipation, health status (p<.001 for each), nausea-vomiting (p= .004), and menstrual changes (p= .001) were found between groups. Overall, physical wellbeing was significantly different between groups (p< .001). Sleep disturbance (84.7% of influence) and appetite changes (75.7% of influence) were the best predictors for determining physical wellbeing in CCS and BCS respectively.Conclusion: More severe cancer symptoms were found in CCS, but more poor perceived health status was found in BCS. There was a significant difference of physical wellbeing found between CCS and BCS.